2020
DOI: 10.1055/a-1193-5170
|View full text |Cite
|
Sign up to set email alerts
|

Gross Motor Skills in Children with Cerebral Palsy and Intellectual Disability

Abstract: Objectives The aim of this study is to determine the connection of gross motor skills (locomotor skills and object control) and the degree of associated intellectual disability (ID) in children with cerebral palsy (CP). Participants and methods The study sample included 54 children with CP and associated ID age 5 years to 6 years and 11 months. For the assessment of tested skills, The Gross Motor Function Classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This is optimistic data, because it is clear that children with ID are under the influence of their parents when it comes to carrying out PA, while the adult population, people with MID for example, is more independent and therefore more physically active in performing daily life activities (Wouters et al, 2019). Forming the habit of conducting PA, as well as gradually increasing the intensity and frequency of exercise and reducing sitting time, should be implemented from the earliest age within the early intervention programme, depending on the abilities of the child with ID (Djuric-Zdravkovic et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is optimistic data, because it is clear that children with ID are under the influence of their parents when it comes to carrying out PA, while the adult population, people with MID for example, is more independent and therefore more physically active in performing daily life activities (Wouters et al, 2019). Forming the habit of conducting PA, as well as gradually increasing the intensity and frequency of exercise and reducing sitting time, should be implemented from the earliest age within the early intervention programme, depending on the abilities of the child with ID (Djuric-Zdravkovic et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research studying PA in the preschool population was conducted with children of typical development. A limited number of studies examines the determinants and correlates of PA within the population of preschool children with ID (Djuric-Zdravkovic et al, 2021). However, even within this small sample of literature, the benefits of PA are noted, and are reflected in the improvement of health and motor problems of children of this population (Collins & Staples, 2017;Wouters et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that in preschool children with CP, there was a considerable link and improvement between the quality of gross motor functions and their intellectual capacity. This should be taken into account when developing a more thorough individual developmental rehabilitation plan for children with CP and intellectual disability, as well as predicting appropriate developmental stimulation methods 23 . Our study on jumping trampoline exercises considerably improved gross motor functions in children with CP, therefore it can be considered in the umbrella of stimulation methods training.…”
Section: Discussionmentioning
confidence: 99%
“…Sistem klasifikacije grubih motoričkih funkcija klasifikuje CP u pet nivoa, po težini. Svaki sledeći nivo u rastućem poretku podrazumeva manji stepen samostalnog kretanja i veća ograničenja u tom domenu (Djuric-Zdravkovic et al, 2021;Palisano et al, 1997). Deca četvrtog i petog nivoa imaju značajno veće šanse da imaju urinarnu inkontinenciju (Jiang et al, 2022;Samijn et al, 2022).…”
Section: Toaletni Trening Kod Dece Sa Cerebralnom Paralizomunclassified